Novel-view synthesis of outdoor sport events using an adaptive view-dependent geometry - Germann, M.; Popa, T.; Keiser, R.; Ziegler, R.; Gross, M. (Computer Graphics Forum, 2012)
We propose a novel fully automatic method for novel-viewpoint synthesis. Our method robustly handles multi-camera setups featuring wide-baselines in an uncontrolled environment. In a first step, robust and sparse point correspondences are found based on an extension of the Daisy features. These correspondences together with back-projection errors are used to drive a novel adaptive coarse to fine reconstruction method, allowing to approximate detailed geometry while avoiding an extreme triangle count.